An Experimental and Theoretical Approach to the Photophysical Properties of Some Rh and Ir Complexes Incorporating the Dipyrromethene Ligand. Issue 12 (13th February 2013) - Ramlot, Diane; Rebarz, Mateusz; Volker, Leen; Ovaere, Margriet; Beljonne, David; Dehaen, Wim; Van Meervelt, Luc; Moucheron, Cécile; Kirsch‐De Mesmaeker, Andrée
Abstract: Rh and Ir complexes that contain meso ‐( p ‐methoxyphenyl)dipyrromethene (dipy) and phenylpyridine (ppy) ligands i.e., [Rh(dipy)3 ], [Rh(ppy)2 (dipy)] and [Ir(ppy)2 (dipy)] have been prepared and their electrochemical and luminescence behaviour are discussed and compared to results of theoretical calculations. The oxidation and reduction potentials, in agreement with the time‐dependent (TD)‐DFT calculations, indicate clearly that the HOMO–LUMO transitions are governed by the dipy ligand, which controls also the triplet excited‐state emission. However, in luminescence, the two Rh complexes exhibit, in addition to a dipy‐centred triplet emission, luminescence from the singlet excited state, which predominates at room temperature, due to a less important influence of the heavy‐metal effect in Rh than in Ir complexes. Although the TD‐DFT results are in very good agreement with the experimental emission spectra from the dipy‐centred triplet excited state, this is not the case for the absorption spectra of the complexes and free dipy ligand. Abstract : The spectroscopic properties of Rh and Ir complexes that contain meso ‐ p ‐methoxyphenyldipyrromethene (dipyH) and phenylpyridine (ppy) ligands, [Rh(dipy)3 ], [Rh(ppy)2 (dipy)] and [Ir(ppy)2 (dipy)], are described and discussed from experimental and theoretical approaches.